Analysis of Factors Influencing Antenatal Care (ANC) Visits at the Waturu Community Health Center, Nirunmas District, Tanimbar Islands District - Dorkas Batilmurik; Yenny Puspitasari; Rahmania Ambarika (STRADA : Jurnal Ilmiah Kesehatan, 2026)
This study aims to analyze the factors that influence Antenatal Care (ANC) visits at the Waturu Community Health Center, Nirunmas District, Tanimbar Islands Regency. Regular ANC visits are essential in preventing pregnancy complications and improving the health of mother and baby. This research uses a quantitative approach with a cross-sectional survey design. The research respondents were 50 pregnant women who were selected using purposive sampling. Data was collected through questionnaires and analyzed using multiple linear regression.